LA PRISE DE CONSCIENCE DES PYGMEES FACE A LEUR ASSERVISSEMENT DANS LE TERRITOIRE D’INGENDE EN REPUBLIQUE DEMOCRATIQUE DU CONGO - BONYONGO, Jean-Louis EYOMA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Marginalized a long time and considered like valets by the bantus, the Pygmy began to become aware of their conditions of life and their unjust social reports with their masters (bantu). This awareness is encouraged below by the factors: the school, the NGO national and international, the Churches. The awareness of the Pygmy, drag positive consequences on the social, political and economic plan. Thus, the social reports between Pygmy and bantus improves, the Pygmy take care of their marriages and don’t disregard the studies anymore. They participate in the vote, adhere to the political parties, get involved in the economic activities as the public transportation, agriculture.